Property verbs in Logba - Dorvlo, K. (Department of Linguistics, University of Ghana, Legon, 2010)
Property denoting expressions can be morpho-syntactically treated as adjectives, verbs or nouns in a language. In Logba such expressions are predominantly verbs. In this paper, I argue for this position by examining their characteristic verbal properties. I demonstrate that property denoting words in Logba encode inherent properties of the entities they are predicated of; they occur in the verbal slot and take subject cross-reference markers; they express non-dynamic situations and a sub-class can even be used in a two argument clause and can participate in causative alternation. Some property verbs can occur in some kinds of serial verb constructions and can be used with the progressive and habitual aspect markers. In addition, two of the words identified in this group take the class changing suffix –yi to form derived adjectives and one of them undergoes reduplication to form a derived adjective
Keywords: Non dynamic situation; pre-verbal argument; causative alternation; property denoting expressions